The Deviation of Law in the Practice of Merariq Kodeq Tradition (Underage Runaway Marriage/Elopement) of the Sasak Community in Lombok, West Nusa Tenggara - Sumerah; Rodliyah; Ginting, Jamin (Faculty of Law, Universitas Pelita Harapan | Lippo Village, Tangerang 15811 - Indonesia, 2025)
There are complex problems of underage runaway marriage/elopement practices in the Sasak community in Lombok, West Nusa Tenggara. Merariq is running off with a girl to make her a wife. The practice of merariq in the Sasak community in Lombok is rife with underage children or what is known as merariq kodeq. The focus of this research is the deviation of law in the practice of merariq kodeq tradition (underage runaway marriage/elopement) of the Sasak Community in Lombok, West Nusa Tenggara. The type of this research is descriptive qualitative with data collection from conducting observations, interviews, documentation and literature studies. The findings of this research show that some of law deviations, including the legalization of child marriage (merariq kodeq/merariq kocet), have brought about the high rate of sirri marriage practice and early divorce, giving effect to the counterproductive dispensation of marriage in the Sasak community in Lombok, high rate of early divorce, and finally has an impact on the increasing numbers of schools’ dropouts. Further investigation of this traditional merariq practice has violated the rights of a minor, and this is within the category of deviation of law, namely the law on child protection and can also be classified as a criminal act. Among the legal issues in the practice of merariq kodeq among the people of Lombok, namely, legal issues of the criminal act of taking away a minor, the criminal act of violence, the criminal act of sexual violence, and the criminal act of neglecting a child. Efforts to prevent the practice of merariq kodeq are urgently needed as in the cases raised in this research, such as reviving local culture/local wisdom with full responsibility. On the other hand, efforts are needed to optimize socialization about marriage; real government intervention is needed in persuasive and educational efforts (a marriage school is needed as a media center); and the importance of carrying out non-litigation efforts on legal issues that arise in the practice of merariq kodeq, namely, maximizing peace efforts between parties, and increasing legal awareness in society in order to prevent people from being entangled in criminal acts and legal processes or legal punishment.